Progressive microneedles for targeting and intelligent drug delivery - Jiaqi Li; Qing Xia; Shuwen Ma; Zhi Wang; Teng Guo; Nianping Feng; Yongtai Zhang (Asian Journal of Pharmaceutical Sciences, 2025)
Microneedle-mediated drug delivery systems (MDDS) have experienced robust growth in recent years, with designers leveraging their creativity to apply these systems for direct drug delivery to the skin, mucous membranes, blood vessel walls and even internal organs. In order to achieve precise drug delivery, various delicately conceived drug release modes based on MDDS have been developed. Herein, to elucidate the design concepts of numerous reported MDDS, we have categorized them into two levels (Level-Ⅰ MDDS and Level-Ⅱ MDDS) depending on whether nanoscale and microscale carriers are integrated within the microneedles. In this work, the design strategies of MDDS, as well as the current status of their applications in targeted and intelligent drug delivery were reviewed, while their prospects and challenges for future industrialization and clinical applications were also discussed.